Analisis Kualitas Pelayanan dan Fasilitas Perpustakaan Terhadap Minat Kunjung Mahasiswa Universitas Negeri Semarang - Avivah, Dyah Rizky; Aulia Prima Kharismaputra (Global Action and Education for Society, 2026)
Libraries are essential academic support facilities in higher education, significantly contributing to teaching and learning activities. The key factor influencing user visitation is the quality of services and facilities. This study aims to evaluate the quality of facilities and librarian performance at the Rumah Ilmu Library, Semarang State University (UNNES), in relation to student visitation interest using the SERVQUAL framework, which includes Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A descriptive qualitative method was applied with a phenomenological approach and purposive sampling. Data were collected through direct observation and in-depth interviews. Results show that while physical facilities are generally adequate, issues remain, such as limited seating and suboptimal supporting amenities. In terms of service, users experienced inconsistent information, delayed responses, and a lack of empathy from staff, reducing trust in library services. Therefore, comprehensive improvements in both facilities and service quality are necessary to meet user expectations and increase student interest.